2017
DOI: 10.3892/ijmm.2017.2872
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-2 enhances the osteogenic differentiation capacity of mesenchymal stromal cells derived from human bone marrow and umbilical cord

Abstract: Mesenchymal stromal cells (MSCs) are multipotent cells that can give rise to different cell types of the mesodermal lineages. They are powerful sources for cell therapy in regenerative medicine as they can be isolated from various tissues, and can be expanded and induced to differentiate into multiple lineages. Recently, the umbilical cord has been suggested as an alternative source of MSCs. Although MSCs derived from the umbilical cord can be induced to differentiate into osteoblasts with a phenotypic similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 40 publications
(49 reference statements)
7
53
0
Order By: Relevance
“…MSCs isolated from human umbilical cord (hUCMSCs), which is routinely discarded as clinical waste, has the similar capacities of cell proliferation, differentiation and immunosuppression to human bone marrow MSCs (Ennis, Gotherstrom, Le Blanc, & Davies, 2008;Ullah, Subbarao, & Rho, 2015). hUCMSC has been demonstrated to be a promising alternative source of MSC (Hou et al, 2009;Klontzas, Kenanidis, Heliotis, Tsiridis, & Mantalaris, 2015;Marupanthorn, Tantrawatpan, Kheolamai, Tantikanlayaporn, & Manochantr, 2017). However, the role and mechanism of the hUCMSCsecreted ECM constructs (hUCMSC-ECM) on bone formation remain unknown in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs isolated from human umbilical cord (hUCMSCs), which is routinely discarded as clinical waste, has the similar capacities of cell proliferation, differentiation and immunosuppression to human bone marrow MSCs (Ennis, Gotherstrom, Le Blanc, & Davies, 2008;Ullah, Subbarao, & Rho, 2015). hUCMSC has been demonstrated to be a promising alternative source of MSC (Hou et al, 2009;Klontzas, Kenanidis, Heliotis, Tsiridis, & Mantalaris, 2015;Marupanthorn, Tantrawatpan, Kheolamai, Tantikanlayaporn, & Manochantr, 2017). However, the role and mechanism of the hUCMSCsecreted ECM constructs (hUCMSC-ECM) on bone formation remain unknown in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblast‐derived osteocalcin, osteonectin, and FGF23 have opposing effects for bone matrix formation . BM stromal cells secrete BMP2, which enhances the osteoblast differentiation from MSCs and osteoblast functions . Accumulated adipocytic cells in BM lead to generation of DPP4, which impairs bone regeneration .…”
Section: Resultsmentioning
confidence: 99%
“…Osteoblasts are mainly derived from bone marrow mesenchymal stem cells, the differentiation process of which is dependent on the regulation of a number of transcription factors and cytokines (20). Bone marrow mesenchymal stem cells are pluripotent stem cells that can differentiate into osteoblasts, chondrocytes and adipocytes (21). A previous study revealed that when the cells have high expressions of Runx2 and OSX, mesenchymal stem cells are differentiated into osteoblasts (21).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells are pluripotent stem cells that can differentiate into osteoblasts, chondrocytes and adipocytes (21). A previous study revealed that when the cells have high expressions of Runx2 and OSX, mesenchymal stem cells are differentiated into osteoblasts (21). However, when these cells highly express sex-determining region Y-box 9, mesenchymal stem cells are differentiated into chondrocytes, and when they have a high expression of PPAR, they differentiate into chondrocytes (22).…”
Section: Discussionmentioning
confidence: 99%